Precision COVID-19 Vaccine with Companion Diagnostics - Julianna Lisziewicz (Precision Nanomedicine)
Although disease enhancement by antibodies has been described for corona and other viruses, nobody can predict whether such antibodies induced by the vaccine will not be harmful, especially after reinfection with a different strain. Alternative vaccines could induce memory T-cell responses, in the absence of antibodies, to kill newly infected cells. Preclinical testing of such precision vaccines is performed in silico without animal experiments since epitopes predicted to bind to three HLA class I molecules of a subject activate cytotoxic T-cell response with more than 80% probability. Data science can be utilized to select the immunogenic vaccine peptides from the coronavirus replicase protein and estimate the immune response rate in an HLA-genotyped population. Employing accessible platform technologies, a set of precision vaccines could be co-developed with an HLA-genotype based companion diagnostic to identify the vaccine that most likely induces responses in the subject. The goal of precision vaccination is to convert the deadly COVID-19 into asymptomatic disease and to avoid the potential risk of disease enhancement.